Evaluation of the engineered polysaccharide alpha‐1, 3 glucan in a thermoplastic polyurethane model system. Issue 9 (18th September 2020) - Mok, Jorge Wu; Behabtu, Natnael; Lenges, Christian; Sendijarevic, Ibrahim; Sendijarevic, Aisa
Abstract: Enzymatic polymerization is under development as novel scalable process technology to convert sucrose to engineered polysaccharides. Similar to established monomer‐based polymerization processes, this approach allows for the synthesis of glucose‐based polymers with controlled polymer linkage, structure, and material morphology. Using enzymatic polymerization, alpha‐1, 3‐polyglucose (glucan) can now be produced from sugar on scales required for industrial applications. This alpha‐1, 3 glucan material, with accessible primary and secondary hydroxyl groups within the overall defined particle morphology, is especially of interest as a partially reactive component in polyurethane chemistry. This study explores the impact of alpha‐1, 3‐glucan as additive in a thermoplastic polyurethane model system and the improvement in mechanical properties of these composites. Glucan was effectively first mixed with a polyether polyol diol, forming a stable dispersion with narrow particle size distribution, followed by reaction with diisocyanate and chain extender to form the polyurethane matrix. The analysis of the generated polyurethane matrix indicates that the hydroxyl groups of the dispersed glucan particles directly react with isocyanate. Tetrahydrofuran solubility of the formed polyurethane compound decreased with the addition of glucan, providing evidence of covalent bonding of glucan leading to cross‐linking of the polyurethane matrix. Thermal analysis of this model system suggests that the glucan additive induces hard segment crystallization, resulting in increased hardness and tensile modulus compared with the reference. Based on the observed property enhancements, engineered polysaccharides provide a sustainable performance additive for polyurethane materials. Abstract : Enzymatic polymerization to produce the engineered polysaccharide alpha‐1, 3 glucan enables unique particle morphologies with reactive hydroxyl groups. The use as reactive component in thermoplastic polyurethanes shows impact on morphology and composite properties. Hydrogen‐bonding between the polysaccharide and the urethane‐hard segment is proposed which impacts the mechanical and dynamic properties of the polymer composite. Based on the observed property enhancements, engineered polysaccharides function as sustainable performance additives extending the TPU application range and also overall composite sustainability.